In praise of emigration and Bill Lidicker’s classic 1962 paper - Krebs, Charles J. (THERYA, 2022)
In 1962 Bill Lidicker, a budding young biologist at Berkeley’s Museum of Vertebrate Zoology, published a short paper on the possibility that emigration might be involved in population regulation. He discussed this possibility largely with respect to small mammals and the possibility that genetic differences might be involved in emigration behavior. The paper contained no data, but it generated much interest in both the ecology and the genetics of emigration. I review in this paper how this stimulus to study emigration developed in the 60 years since Bill Lidicker opened this door for mammalian studies. The first attempts to analyze emigration involved removal experiments, carried out mostly on small rodents, which showed that many individuals could be attracted to an empty habitat via experimental removals. This finding influenced both important issues in pest control and theoretical questions about the quality of emigrants in natural populations. The idea that emigrants might be genetically distinct from resident individuals was gradually abandoned since studies of social organization and in particular territoriality and infanticide focused on social interactions over space in small rodents. Further studies of emigration blossomed in behavioral ecology as more and more studies were carried out on interactions over resources in many other vertebrates. Some generality has been achieved by a focus on the simple questions put forward in this short paper by Bill Lidicker in 1962.